PENGARUH KREATIVITAS DAN MENTAL BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN BISNIS STAMBUK 2022 FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN - Friska Octaviani Br Samosir; Aurora Elise Putriku (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of creativity and entrepreneurial mindset on entrepreneurial interest in Business Education students of the 2022 Stambuk Program, State University of Medan. This study uses a quantitative approach with an ex post facto method. The study population consisted of 63 students, all of whom were sampled using a total sampling technique. The data collection instrument used was a research questionnaire on creativity, entrepreneurial mindset, and entrepreneurial interest in the form of a likert scale, each with 20 items. The results of data analysis using multiple regression and hypothesis testing concluded that creativity and entrepreneurial mindset on entrepreneurial interest. This can be seen from the results of multiple linear regression obtained the equation Y = 20.785 + 0.462 (X1) + 0.234 (X2) + e. Furthermore, data were collected using a Likert scale questionnaire and analyzed by multiple linear regression through the t test, F test, and coefficient of determination (R²). The results of the study show that creativity has a positive and significant effect on entrepreneurial interest (tcount > ttable where. 5.431 > 2.000 with a significant value of 0.000 < 0.005. Likewise, entrepreneurial mentality also has a positive and significant effect on entrepreneurial interest (tcount > ttable where 2.654 > 2.000 with a significant value of 0.000 < 0.005. Simultaneously, both variables have a positive and significant effect on the interest in becoming a teacher (Fcount > Ftable where 61.903 > 3.15 and a significant value of 0.000 < 0.05 so that it can be done that the hypothesis is accepted. Thus, creativity and entrepreneurial mentality have a positive and significant effect on the entrepreneurial interest of business education students, batch 2022, Faculty of Economics, State University of Medan.